2012
DOI: 10.1007/s12253-012-9502-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel Genetic Mutation in the Background of Carney Complex

Abstract: Carney complex is a rare disease inherited in an autosomal dominant manner. It is mostly caused by inactivating mutations of the subunit of protein kinase A. Carney complex is associated with atrial myxoma, nevi or myxomas of the skin, breast tumor and endocrine overactivity. Primary pigmented nodular adrenocortical disease is the specific endocrine manifestation. The authors present the history of a 53-year-old female patient who had undergone surgery for atrial myxomas, thyroid tumor and breast cancer. She w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…The incidence of TC is about 15% [245]. The patients usually develop welldifferentiated carcinomas, both FTC and PTC, sometimes after a long history of multiple adenomas [241,244,256,257]. Hürthle cell adenoma has been reported in a boy with CNC [258].…”
Section: Pathological Featuresmentioning
confidence: 99%
“…The incidence of TC is about 15% [245]. The patients usually develop welldifferentiated carcinomas, both FTC and PTC, sometimes after a long history of multiple adenomas [241,244,256,257]. Hürthle cell adenoma has been reported in a boy with CNC [258].…”
Section: Pathological Featuresmentioning
confidence: 99%
“…DNA was isolated from peripheral blood, and polymerase chain reaction (PCR) followed by bidirectional DNA sequencing was used to test the PRKAR1A gene as previously described 14 .…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 20% of the families affected with Carney complex have 2p16 mutations. To date, there are at least 117 pathogenic variants in PRKAR1A that have been identified [4-7]. In this study, we identified a PRKAR1A mutation, c.491_492delTG, in both patients.…”
Section: Discussionmentioning
confidence: 80%
“…It is less commonly caused by a variety of genetic changes on chromosome 2p16. Currently, 117 different PRKAR1A mutations have been identified [4-7]. Herein, we identify two Chinese Carney complex patients that are siblings with a 491_492delTG PRKAR1A gene mutation.…”
Section: Introductionmentioning
confidence: 99%